Detection of creatinine using silver nanoparticles on a poly(pyrrole) thin film-based surface plasmon resonance sensor - Chammari Pothipor (2020)
© 2019 The Japan Society of Applied Physics. Surface plasmon resonance (SPR) technique is a great tool to investigate the binding of analyte to functionalized surfaces and the immobilization of biomolecules. Creatinine is one of the biomarkers for monitoring renal functions and making a diagnosis of kidney disease. Elevated creatinine levels in the human body signifies impaired kidney disease. In this work, we developed a new strategy for creatinine detection using starch stabilized silver nanoparticles (starch-AgNPs) on poly(pyrrole) (PPy) thin film using the SPR technique. The assay exhibited the obvious change from yellow to orange color of AgNPs solution in the presence of creatinine, showing good sensitivity due to the localized plasmon effect of AgNPs. Based on this effect, the change of SPR reflectivity in the Kretschmann configuration was enhanced by the adsorption of AgNPs in the presence of creatinine on the PPy film. The SPR reflectivity upon the injection of the mixed solution on the PPy thin film increased with increasing creatinine concentration in the linear range from 10 to 1000 μM. As a comparison, performances of the creatinine sensor with three SPR sensor systems, i.e. only PPy film, PPy film with AgNPs, and PPy film with aggregated AgNPs, were studied. The SPR sensor with aggregated AgNPs was improved approximately four times compared with the substrate without aggregated AgNPs, and the limit of the detection was 0.19 μM. The proposed method is potentially useful for clinical applications.